Students' creative thinking ability in solving problems with double loop problem solving model - Dewi, Octia Ayu Shinta; Winarti, Endang Retno (Unnes Journal of Mathematics Education, 2019)
This study aims to test the completeness students' creative thinking abilities of Double Loop Problem Solving for, whether students' creative thinking skills in Double Loop Problem Solving learning are better than Problem Based Learning, the effect of learning independence on students' creative thinking abilities with Double Loop Problem Solving, and describing creative thinking abilities students in terms of learning independence. This research used mixed methods with sequential explanatory design. The quantitative research design used was Quasi-Experimental Design in the form of Posttest-Only Control Group Design The subjects of this study were six students of VIII C Class in SMPN 35 Semarang in the even semester of academic year 2018/2019. The data collection techniques used were: tests, questionnaires, and interviews. The results showed that: (1) students 'creative thinking ability in Double Loop Problem Solving learning achieves classical completeness, (2) students' creative thinking ability with the Double Loop Problem Solving model is better than Problem Based Learning, (3) learning independence has a positive effect on students' creative thinking ability in Double Loop Problem Solving learning, (4) students' creative thinking skills in terms of learning independence in Double Loop Problem Solving learning model as follows (a) Subjects with low group learning independence are less able to solve problems correctly and smoothly, with the different ways or answers, with their own thoughts, and with details; (b) Subjects of medium group learning independence are able to solve problems correctly and smoothly, less able to solve problems in different ways or answers, able to solve problems with their own thoughts, and less able to solve problems in detail; (c) Subjects of high group independent learning above are able to solve problems correctly and smoothly, with different ways or answers, with their own thoughts, and with details